A patient with back pain: therapy possibilities - P. R. Kamchatnov; A. V. Chugunov; E. A. Trubetskaya (Нервно-мышечные болезни)
Low back pain (LBP) is one of the most common clinical syndromes associated with the high rate of temporary disability and sizable material costs. The choice of adequate therapy for LBP requires that primary diseases that can be responsible for the occurrence of pain should be excluded. While choosing an analgesic, there must be a balance between its efficacy and the possible risk for undesirable side effects. One of the drugs that have proven effective in treating patients with LBP is ketoprofen (ketonal), the diversity of whose formulations allows maximally individualized therapy.